Chinese patent medicine as a complementary and alternative therapy for type 2 diabetes mellitus: A scoping review - Hai-Zhu Zheng; Tian-Ying Chang; Bo Peng; Shi-Qi Ma; Zhen Zhong; Jia-Zhen Cao; Lin Yao; Meng-Yuan Li; Hong-Feng Wang; Xing Liao (Elsevier, 2024)
Objective: This scoping review aims to document Chinese Patent Medicines (CPMs) for Type 2 Diabetes Mellitus, explore whether CPMs can improve patients' health outcomes, and set priorities in addressing research gaps in this area. Methods: Following the framework of PRISMA-SCr, we proposed the research questions based on PICOS principle, and searched the CPMs for T2DM from three drug lists, followed by a systematic search of the literature in eight databases from their inception to June 22, 2023. Then, we developed the eligibility criteria and systematically reviewed the relevant studies, retained the studies about CPMs for T2DM, extracted the related data, and identified the differences across studies in structured charts. Results: A total of 25 types of CPMs were extracted from the three drug lists. Radix astragali appeared most frequently (19 times) among the herbal medicinal ingredients of CPMs. A total of 449 articles were included in the full-paper analysis ultimately, all of which were about 20 types of CPMs, and there were no related reports on the remaining five CPMs. Except about a quarter (25.39 %, 114/449) using CPMs alone, the remaining studies all involved the combination with oral hypoglycemics for T2DM. Biguanides are the most common drugs used in combination with CPMs (50.14 %, 168/335). Fasting plasma glucose (FPG) is the most frequently reported outcomes in efficacy evaluation (82.41 %, 370/449). Conclusion: There are a total of 25 types of CPMs currently available for T2DM patients. However, the volume of related evidence on these CPMs varies. It is necessary to standardize the combined use of CPMs and conventional medicine and select appropriate outcomes in future studies.